The college devaluation crisis market disruption, diminishing ROI, and an alternative future of learning - Wingard, Jason (Tantor Media, Inc., 2022)
The value proposition of the college degree, long the most guaranteed route to professional preparation for work, is no longer keeping pace with rapidly evolving skill needs that derive from technological advancements impacting today's work force. If the university system does not engage in responsive restructuring, more and more workplaces will bypass them entirely and, instead, identify alternative sources of training that equip learners with competencies to directly meet dynamic needs. The College Devaluation Crisis makes the case that employers and other learning and development entities are emerging to innovate new approaches to training talent that, at times, relies on the higher education sector, but increasingly operates independently in order to satisfy talent needs more agilely and effectively. Targeted primarily toward managers, the book focuses on case studies from leading companies, including Google, Ernst & Young, IBM, and Marriott, to illustrate their innovative strategies for talent development across varying levels of individual education, age, and background. The book also addresses professionals on the university side, urging listeners to consider the question: Will higher education pivot and adapt, or will it resist change and, therefore, be replaced?
Online resource; title from title details screen (O'Reilly, viewed July 27, 2022)
Keywords: Labor supply -- Effect of education on -- United States; Employees -- Training of -- United States; College graduates -- Employment -- United States; Vocational qualifications -- United States; Education, Higher -- Economic aspects -- United States; Marché du travail; Effets de l'éducation sur; États-Unis; Personnel; Formation; États-Unis; Qualifications professionnelles; États-Unis; Enseignement supérieur; Aspect économique; États-Unis; College graduates; Employment; Education, Higher; Economic aspects; Employees; Training of; Labor supply; Effect of education on; Vocational qualifications; United States; Downloadable audio books; Audiobooks; Livres audio